2020
DOI: 10.35946/arcr.v40.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol�s Effects on Breast Cancer in Women

Abstract: Globally, more than 2 million new cases of breast cancer are reported annually. The United States alone has more than 496,000 new cases every year. The worldwide prevalence is approximately 6.8 million cases. Although many risk factors for breast cancer are not modifiable, understanding the role of the factors that can be altered is critical. Alcohol consumption is a modifiable factor. Studies of alcohol in relation to breast cancer incidence have included hundreds of thousands of women. Evidence is consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 79 publications
0
48
0
1
Order By: Relevance
“…Additionally, for women, alcohol levels in the blood rise faster and stay elevated longer compared to men [ 44 ]. Alcohol consumption is further known to effect estrogen signaling in the body, and just 10–15 g/day (one drink) was associated with a higher risk of breast cancer in women [ 10 ]. Although being a female sex is associated with a higher risk of RA, the exact effect of estrogen on RA risk is not clear [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for women, alcohol levels in the blood rise faster and stay elevated longer compared to men [ 44 ]. Alcohol consumption is further known to effect estrogen signaling in the body, and just 10–15 g/day (one drink) was associated with a higher risk of breast cancer in women [ 10 ]. Although being a female sex is associated with a higher risk of RA, the exact effect of estrogen on RA risk is not clear [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Female sex is a well-established risk factor for RA [ 9 ]. The association between alcohol consumption and RA risk may be different in men and women because the effect of alcohol on estrogen signaling [ 10 ] and the hypothalamic-pituitary-adrenal (HPA) axis [ 11 , 12 ], which may be associated with RA risk [ 13 , 14 ]. To date, only one case-control study reported associations between alcohol consumption and RA risk stratified by sex [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In “Alcohol’s Effects on Breast Cancer in Women,” Freudenheim highlights the compelling evidence that any alcohol use increases breast cancer risk and that risk increases as total consumption increases, emphasizing the importance of targeting this modifiable risk factor for public education and intervention. 25 Current findings suggest that these effects are independent of alcohol beverage type or age at alcohol exposure. The author reviews possible mechanisms for this increased risk including direct carcinogenic effects of alcohol and acetaldehyde, changes in hormones associated with drinking, and alterations in DNA methylation.…”
mentioning
confidence: 81%
“…The author reviews possible mechanisms for this increased risk including direct carcinogenic effects of alcohol and acetaldehyde, changes in hormones associated with drinking, and alterations in DNA methylation. 25 …”
mentioning
confidence: 99%
“…Nutritional and lifestyle habits such as the consumption of alcohol, high-calorie diets, obesity and physical inactivity contribute to breast cancer initiation and/or promotion [ 14 ]. For example, alcohol consumption increases the steroid hormone levels, which, in turn, alters the DNA methylation status by affecting one carbon metabolism [ 15 ]. A high-calorie intake with reduced physical activity led to an increase in the body mass index (BMI).…”
Section: Mechanisms Underlying Breast Cancermentioning
confidence: 99%